In situ catalytic conversion of tar using rice husk char/ash supported nickel–iron catalysts for biomass pyrolytic gasification combined with the mixing-simulation in fluidized-bed gasifier. (15th December 2015) - Shen, Yafei; Zhao, Peitao; Shao, Qinfu; Takahashi, Fumitake; Yoshikawa, Kunio
Highlights: Tar can be in situ converted by the RHC/RHA supported nickel–iron catalysts. The tar conversion efficiency could reach about 92.3% by the RHC Ni–Fe. Partial metal oxides in the carbon matrix could be in - situ reduced into the metallic state. Mixing with RHA Ni can also improve biomass fluidization behavior. Abstract: A catalytic gasification technology has been proposed for tar in situ conversion using the rice husk char (RHC) or rice husk ash (RHA) supported nickel–iron catalysts. Biomass tar could be converted effectively by co-pyrolysis with the RHC/RHA supported nickel–iron catalysts at 800 °C, simplifying the follow-up tar removal process. Under the optimized conditions, the tar conversion efficiency could reach about 92.3% by the RHC Ni–Fe, which exhibited more advantages of easy preparation and energy-saving. In addition, the tar conversion efficiency could reach about 93% by the RHA Ni. Significantly, partial metal oxides (e.g., NiO, Fe2 O3 ) in the carbon matrix of RHC could be in-situ carbothermally reduced into the metallic state (e.g., Ni 0 ) by reducing gases (e.g., CO) or carbon atom, thereby enhancing the catalytic performance of tar conversion. Furthermore, mixing with other solid particles such as sand and RHA Ni, can also improve biomass (e.g., RH) fluidization behavior by optimizing the operation parameters (e.g., particle size, mass fraction ) in the mode of fluidized bed gasifier (FBG). After the solid–solid mixing simulation, the RH mass fraction of 0.5 and the particle diameter of 0.5 mm can be employed in the binary mixture of RH and RHA.